(untitled) (Research, Society and Development, 2022)
Objective: To describe the care and health needs of quilombola women, from the perspective of the intersectionality of gender, race, body, and politics, according to evidence published in the scientific literature. Method: This is an integrative literature review, which searched in the following databases: BVS, EBSCO, LILACS, SciELO, MEDLINE, Web of Science, Scopus, Applied Social Sciences Index & Abstracts, and in the Brazilian Digital Library of Theses and Dissertations and CAPES Journal Portal. The descriptors "Quilombola woman", "Black Woman", "Vulnerability", "Health", "Health conditions of Ethnic Groups", "Care Practices", "Self-care", whose combinations used with the Boolean operators AND and OR. The following inclusion criteria: articles, theses, and dissertations available free in the databases for full reading in Portuguese or English, from research in Brazil published between 2008 and 2018. Publications in editorial format excluded debates and reviews. Results: Twenty-three publications analyzed in national databases, which outlined the memories of the ways of life of quilombola women, pointing to the saga of resistance and the fight against racism, patriarchy, sexism, lack of access to health, and the disrespect to their cultural care practices over the ten years of the National Policy for Comprehensive Health for the Black Population. Conclusion: The publications indicate the social inequities experienced by quilombola women, reflections of everyday oppression generated by intersectionality, requiring greater attention from health policies and social rights.